Factors affecting compliance with infection prevention and control standard precautions among healthcare workers in Songwe region, Tanzania. Issue 4 (December 2022) - Bahegwa, Radenta P.; Hussein, Ally K.; Kishimba, Rogath; Hokororo, Joseph; German, Chrisogone; Ngowi, Ruth; Eliakimu, Eliudi; Ngasala, Billy
Summary: Background: Compliance with infection prevention and control standard precautions (IPCSPs) remains a major challenge in many countries including Tanzania. Lack of compliance exposes healthcare workers (HCWs) and patients to a high risk of developing healthcare-associated infections (HAIs) including antimicrobial-resistant microorganisms which can contribute to the spread of antimicrobial resistance (AMR). This study investigated compliance with IPCSPs and associated factors among HCWs in public healthcare facilities (HFs) in Songwe Region, Tanzania between January and March 2021. Methods: A cross-sectional study was conducted in all 5 districts in Songwe Region, involved 400 HCWs from difference healthcare facilities (HFs) including dispensaries, health centres and hospitals. The Compliance with Standard Precautions scale (CSPS) tool developed by WHO was used. Descriptive and modified Poisson regression analysis was done. A P -value of less than 0.05 indicated statistical significance. Results: Only 22.5% (90/400) of HCWs had high compliance (above 80%) to IPCSPs. The majority of HCWs reported highest compliance on discarding used needles/sharps into sharps containers (94%), the lowest IPCSPs compliance was for the correct handling of spills, taking a shower after extensive splashing and not re-using disposable masks, 8%, 28.5% and 34% respectively. Attending IPC training or an IPC seminar in the previous year (ARR=2.97 [1.87–4.72] P <0.001), the number of years of work experience (ARR=2.08 [1.22–3.54] P =0.007), and having experienced a needlestick injury (ARR=0.62 [0.40–0.95] P =0.028), were identified as predictors of HCWs compliance with IPCSPs. Conclusion: The majority of HCWs in Songwe region had low compliance with IPCSPs according to national standards. IPC training and the number of years of work experience predicted high compliance with IPCSPs. Capacity building initiatives, mentorship and supportive supervision should be emphasised for all HCWs in all HFs.